Brazilian Protocol for Sexually Transmitted Infections 2020: sexual violence - Menezes,Maria Luiza Bezerra (2021)
Abstract This article addresses sexual violence, as part of the Clinical Protocol and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections, published by the Brazilian Ministry of Health. Guidance is provided in programmatic and operational management, focusing on the service network for people in situation of sexual violence, recommendations to health staff about pregnancy and viral and non-viral sexually transmitted infections prophylactic measures, in addition to surveillance action strategies. Sexual violence is an encompassing issue that includes wider areas than the health field. It involves conceptual and programmatic challenges for health staff, at the forefront of care for affected people and also to the implementation of prevention strategies addressed to the whole society.